THE APPLICATION OF APKM (ACCESS, PARTICIPATION, CONTROL, BENEFIT) AND GENDER EQUALITY IN THE STUDENT EXECUTIVE BOARD IN ISLAMIC UNIVERSITY - Lilik Huriyah; Hotimah Novitasari (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
This study aims to understand the implementation of APKM (Access, Participation, Control, and Benefit) and gender equality in the Student Executive Board (BEM) in UIN Sunan Ampel Surabaya (UINSA). The study used a qualitative approach by interviewing members of BEM across nine faculties, administering questionnaires, and collecting relevant documents regarding gender equality. The results indicated that six of BEM had socialised gender equality in their community, and three of them had not promoted it yet. Even though the six BEM claimed that they had promoted gender equality in their community, practically the organisation management did not fully apply gender equality as proved by the election of the leader of executive board is consistently dominated by male students. Female is chosen to hold the job of secretary or treasurer. This is evidence that the management of the organisation has not fully implemented gender equality; there is still a belief that different genders should hold particular positions. The results also demonstrated that women frequently handle household duties like meal preparation and office work when organising events. Contrarily, men are employed to carry out routine jobs. The study shows that although male students currently dominate the competition for the top positions in BEM, both male and female members of the organisation have access to, participation in, control over, and benefits related to gender equality. This may be influenced by patriarchy culture in the community and less awareness of gender equality among members of BEM in UINSA